VB6 : eat vegan every day before 6:00 pm to lose weight and restore your health... for good - Bittman, Mark (Clarkson Potter/Publishers, 2013)
"The best-selling author and popular NYT columnist gives us his innovative and easy diet plan, complete with recipes--by eating vegan every day before 6:00pm, you can lose weight and dramatically improve your health. Every day we learn new benefits of the vegan diet, and discover how cutting meat and animal products out can still mean a world of delicious meals. Now Mark Bittman brings his expertise to vegan cooking, giving you an easy-to-follow diet plan plus 50 simple everyday recipes--exclusively vegan meals for breakfast and lunch, and as flexible as you need to be for dinner. Building on his hit book Food Matters, Bittman outlines in six principles the reasons that a partially vegan diet can dramatically improve your health. When you eat lots of fruits and veggies while cutting back on meat and dairy, and cook as much as possible at home, you automatically find yourself eating more sensible portions and almost no junk food. You can live healthier, not just eat healthier, when you eat with eyes wide open. This is Bittman's flexible, ethical way of eating better and losing weight, using common sense in the kitchen"--